Comparative stability analysis of droop control approaches in voltage-source-converter-based DC microgrids - Gao, Fei; Bozhko, Serhiy; Costabeber, Alessando; Patel, Chintanbai; Wheeler, Patrick; Hill, Christopher Ian; Asher, Greg (IEEE, 2016)
Droop control has been widely applied in DC microgrids (MGs) due to its inherent modularity and ease of implementation. Among the different droop control methods that can be adopted in DC MGs, two options have been considered in this paper; I-V and V-I droop. I-V droop controls the DC current depending on the DC voltage whilst V-I droop regulates the DC voltage based on the output current. The paper proposes a comparative study of V-I/I-V droop control approaches in DC MGs focusing on steady-state power sharing performance and stability. The paper presents the control scheme for current-mode (I-V droop) and voltage-mode (V-I droop) systems, derives the corresponding output impedance of the source subsystem including converters dynamics and analyzes the stability of the power system when supplying constant power loads. The paper investigates first the impact on stability of the key parameters including droop gains, local control loop dynamics and number of sources and then performs a comparison between current-mode and voltage-mode systems in terms of stability. In addition, a generalized analytical impedance model of a multi-source, multi-load power system is presented to investigate stability in a more realistic scenario. For this purpose, the paper proposes the concept of “global droop gain” as an important factor to determine the stability behaviour of a parallel sources based DC system. The theoretical analysis has been validated with experimental results from a laboratory-scale DC MG.